Age, schooling and Verbal Fluency tasks for the screening of Alzheimer´s disease patients - Goñi-Sarriés, Adriana; López-Goñi, José J.; Granados-Rodríguez, David; González-Jiménez, Angela (Anales de Psicología / Annals of Psychology, 2015)
Introduction. The Verbal (VF), Semantic (SF) and Phonemic Fluency (PF) tests are commonly used in clinical practice. Having different alternative tests, that could also allow for the effect of demographic variables, would improve their use as screening tests, making it possible to differentiate patients with or without Alzheimer´s disease (AD). Aims. (1) to compare the discriminatory ability of the SF tasks “things in a house” and “food” versus the task “animals” among patients with the AD (n=50) and healthy subjects (n=50). (2) to compare the use of the phonemes such as “P”, “M” and “R” as an alternative and/or parallel task to the phonemes “F”, “A” and “S”. (3) to asses the combined use of both tasks with the demographic variables for the screening of AD patients and the healthy ones. Results. Both semantic and phonemic categories indicate similar results, high correlation, support the criteria validity and allow for their use in a parallel way. Among all the different roles assessed, the most successful in screening correctly 91% of the evaluated subjects is the one that includes tasks such as “things in a house”, the phonemes “A” and “S” and the age and schooling time variables. Conclusion. The parallel use of VF and PF, plus the demographic variables improve the discriminatory ability of the VF tests.